Analysis of Corrosion Prediction Software for Detection Corrosion in Oil and Gas Evironment Containing Acetic Acid, CO2 and H2S Gases - Asmara, Y. P.; Nur Azhani, Abd Razak; Salwani, Mohd Salleh (2014)
Corrosion Prediction models are important tools in determining materials selection and managing corrosion control strategies. The models can also be used as input in the Corrosion Design Basis Memorandum (CDBM). However, most of the corrosion prediction models have limited parameters as inputs in calculating corrosion rate. They emphasize only for specific environmental conditions. Thus, the models will be inaccurate in evaluating the corrosion rate when multi species and complex corrosion mechanisms exists. This research studied models developed by industries and academia which are ECE, Cassandra, Norsok, and Freecorp. This paper evaluated prediction model based on their theoretical backgrounds in CO2 environments pipelines which transports oil/gas/water by comparing with literatures and data’s experiments. Corrosion experiments were carried out to propose a model prediction using semi empirical approach.